Diabetes and oral health - Misztal, Zofia; Pawlicka, Marta; Mroczek, Anna; Bałabuszek, Kamil; Ochyra, Dorota; Pawlicki, Mateusz (Journal of Education, Health and Sport, 2018)
The main aim of this review is to pay attention to correlation between increasingly common disease all over the world which is diabetes and oral cavity disorders. There were many retrospective studies and researches which improve this relationship but in some of them there exist doubts. There occurs two-way link between this diseases. On one way diabetes may increase the risk of developing periodontitis and on the other periodontal disorders might have impact on glycaemic control. In some cases was reported that periodontitis have influence on appearance of other complications not related to diabetes such as cardiovascular diseases, proteinuria, stroke, angina, retinopathy. Appropriate oral hygiene and controlling the diabetes leads to better glycaemic control and lower play scores and lower HbA. There is need to cooperation between physical and dentists to improve better condition of oral cavity to patients with diabetes and to better glycaemic control.